Antioxidant Effect of a Dietary Supplement Containing Fermentative S-Acetyl-Glutathione and Silybin in Dogs with Liver Disease - Elisa Martello; Francesca Perondi; Donal Bisanzio; Ilaria Lippi; Giorgia Meineri; Valeria Gabriele (Veterinary Sciences, 2023)
Oxidative stress is often involved in liver disease progression. Liver is the primary site for the synthesis of glutathione (GSH), the major intracellular antioxidant. GSH erythrocyte concentration can decrease in case of liver damage. So, the use of food supplements with antioxidant capacity has been reported in the veterinary literature. In this case–control study, we tested a new supplement containing S-acetyl-glutathione (SAG), silybin, and other antioxidant ingredients in dogs affected by liver disease. After two weeks of supplement administration, we were able to report a significant increase in the level of erythrocyte GSH in the treated (TRT) group, nearly reaching the physiological limit at the end of the study. In addition, most of the key liver parameters are significantly reduced in the TRT group by the end of the trial. The results of this study support the effectiveness of the tested complementary feed, which may be helpful in managing dogs with liver conditions.